Repression, rivalry and racketeering in the creation of Franco’s Spain: the curious case of Emilio Griffiths - Stockey, Gareth (Sage, 2018)
This article charts the personal history of Emilio Griffiths Navarro, a key individual in the Francoist administration in the Campo de Gibraltar (Cádiz province) during the early months of the Spanish Civil War. Griffiths is used as a case study to analyse the dynamics of Francoist repression in Southern Spain, and in particular the construction of what Rúben Serém has referred to as the ‘kleptocratic state’ that Franco’s fellow conspirator, General Queipo de Llano, constructed in the South. The article reaffirms the degree to which personal networks, personal rivalries and personal gain played a role in the Francoist repression. As a local case study, it also notes the unique conditions provided by rebel Spain’s border with British Gibraltar, and how this shaped the nature and extent of that repression. The article charts Griffiths’ own demise, from senior rebel official to arrest and unexplained death at the hands of Francoist security forces just ten months later, and uses the mystery to further speculate as to rivalries and repression in early-Francoist Spain